Grace : a memoir - Coddington, Grace; Roberts, Michael (London : Chatto & Windus, 2012)
Overnight, the flame-haired the author became a heroine for fashion insiders and the general public alike. This title shares the excitement and vision that go into producing so many unforgettable fashion images.
Introduction -- On growing up -- On modeling -- On the fashionable life -- On British Vogue -- On taking pictures -- On beginnings and ends -- On cafe society -- States of grace -- On Ruce -- On Didier -- On Calvinism -- On Anna -- On American Vogue -- On the bigger picture -- On pushing ahead -- On Liz.
boek
Keywords: Coddington, Grace